The Changing Tide of Immigration and Emigration During the Last Three Centuries - Muenstermann, Ingrid (2023)
This book demonstrates the tide of change of immigration and emigration. Societies of the northern part of the globe, which had previously sent people to developing countries in the southern hemisphere, are experiencing a never-ceasing influx of registered and unregistered people from the southern part of the globe. In thirteen chapters written by experts from all over the world, this book explores emigration and immigration during the last three centuries.